Dimensões de variação dos reality TV shows norte-americanos: análise e tipologia textual multidimensional - Araújo, Rafael Fonseca de (2023)
The goal of this study is to investigate and identify dimensions of variation in the language of North American Reality TV shows. To the end, a Multidimensional Analysis (BIBER, 1988 et seq.; BERBER SARDINHA, 2004 et. seq.) and a Textual Typology Analysis (BIBER, 1989 et seq.; BERBER SARINHA, VEIRANO PINTO, 2021) of the Corpus of American Reality TV Shows (CARTS) was carried out. Reality TV shows can be described as unscripted television programs, with non-professional actors being observed by cameras in pre-configured environments (KAVKA, 2012) and despite being a relatively new television genre, it is considered a milestone in television programming in the US, as it reinvented television culture (MURRAY and QUELLETTE, 2004). The corpus consists of 780 texts extracted from 39 popular North American reality TV shows, totaling more than 6 million words. The corpus texts were classified into four main categories – Competition, Documentary, Talent and Profession, and Transformation – which, in turn, were subdivided into 13 subcategories named: celebrities, dating, game-documentary, soap-opera-documentary, hidden and portable cameras, reality sitcom, business, cooking, fashion, stage performers, expert mentoring, self-improvement, and social experiment. The corpus was balanced so that each category had the same number of texts, grammatically tagged with the Biber Tagger and processed by the Biber Tag Count, which calculates the normalized frequency of the 128 linguistic variables considered in the study. The results of the Multidimensional Analysis identified four dimensions of grammatical variation and the Textual Typology through the statistical analysis of Clusters, grouping the types of reality TV shows according to their multidimensional profile, five textual types of reality TV shows were identified. Since there are no previous studies, within Corpus Linguistics, dedicated to the investigation of linguistic variation and textual typology of reality TV shows, describing the language of this register is fundamental for the studies of variation and typology of register and the present research intends to fill this gap and yet